Pengaruh Pemberian Ekstrak Daun Gulma Siam (Chromolaena odorata L.) dan Lama Perendaman Terhadap Pengawetan Cabai Merah (Capsicum annum L.) - Endang Rizeki; . Supriatno; . Samingan (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2016)
This study aims to (1) determine the concentration of leaf extract weeds siam against the brightness of the color, texture and freshness on red pepper, (2) determine the length of immersion extract of leaves of weeds siam against the brightness of the color, texture and freshness on red pepper, (3) know the siam weed leaf extract concentration and soaking time on levels of vitamin C in red chili. The method used is an experimental method by using a randomized block design pattern (RAK) factorial consisting of 25 treatment combinations each with four replications. There are two factors studied were the first factor leaf extract concentration weed siam consists of 5 levels: P0 (control), P1 (125,000 ppm extract), P2 (250,000 ppm extract), P3 (375,000 ppm extract), P4 (500,000 ppm extract ) and the second factor soaking period consists of 5 levels: L0 (0 min), L1 (15 min), L2 (30 minutes), L3 (45 minutes) L4 (60 minutes). Data were analyzed by analysis of variance (ANOVA) and Least Significant Difference test (BNT0,05). The results showed that the concentration of water extract of siam weed leaves no significant effect (P 0.05) to the brightness and freshness of red chilli to 24 HSP, but otherwise significantly affect the texture of red chili with extract concentrations of 125,000 ppm, 250,000 ppm and 375,000 up to 16 ppm HSP. 0 minutes soaking time was highly significant (P 0.05) to the brightness and freshness of red chilli to 16 HSP and the texture of red chili with a soaking time 45 minutes to 20 HSP. The highest concentration of vitamin C contained in the extract concentration of 375,000 ppm with a soaking time of 60 minutes. The conclusions of this study are siam weed leaf extract and soaking time effect on the brightness of the color red chilli at a concentration of 125,000 ppm with 30 minutes soaking time while the texture of red chili peppers at a concentration of 375,000 ppm with soaking time 0 minutes. However, contrary siam weed extract and soaking time has no effect on the level of freshness of red pepper. The advice can be given in order to further research into better and perfect, ie testing siam weed leaf extract bioactivity against fungi and bacteria that play an important role in the decay of red chili.